SANBERNARDASPIS PYGACANTHA NOV. GEN. ET NOV. SP. (TRILOBITA-ASAPHIDAE) DEL CERRO SAN BERNARDO, SALTA, REPUBLICA ARGENTINA (Ameghiniana, 2013)
In this paper Sanbernardaspis pygacantha nov. gen. et nov. sp. is described and its relations are discussed. The species were collected in the Lower Arenigian sandstones of San Bernardo Hill, Salta.